A taxonomic and gross morphological study of freshwater and brakishwater mollusk of Balion River, Ormoc City, Leyte - Romero, Daniel Dennis Granali; Cordero, Paciente A. (Tacloban City Arts and Sciences Division, University of the Philippines Visayas Tacloban College, 1998)
Altogether, 20 species of Mollusks were found and identified of the 10 collecting stations that were established along the Balion river, Ormoc City, Leyte of these 8 stations are in Freshwater and 2 from the Brackishwaters.
Among the 20 species only Thiaridae that is abundant and widely distributed. Its abundance and wide distribution can be attributed to its Parthenogenetic mode of reproduction.
Of the 20 species, (18 were Gastropods and 2 were Bivalves) 8 families are represented. And they are Neritidae, Cerithidae, Potamididae, Thiaridae, Viviparidae, Littorinidae, Lucinidae and Corbiculidae
Species of Freshwater mollusks were completely absent in Brackishwater.
Undergraduate thesis (Bachelor of Science in Biology) -- University of the Philippines, Tacloban.